Improving Student Learning Outcomes on Prayer Procedures through Direct Practice Methods in Class V of SD Negeri 101024 Sigoring-goring - Hasibuan, Samsinar (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to improve students' learning outcomes in understanding and practicing prayer procedures through direct practice methods in class V of SDN 101024 Sigoring-goring. This study is a Classroom Action Research (CAR) conducted in two cycles, where each cycle consists of stages of planning, action implementation, observation, and reflection. The subjects of this study were 10 students of class V of SDN 101024 Sigoring-goring. Data were collected through observation, evaluation tests, interviews, and documentation, then analyzed using quantitative and qualitative analysis techniques. The results showed that the application of the direct practice method significantly improved student learning outcomes. Before the action, only 20% of students achieved the Minimum Completion Criteria (KKM). After cycle I, the completion increased to 60%, and in cycle II it reached 90%. In addition, this method also increased students' motivation and active participation in learning. Based on the results of the study, the direct practice method proved effective in improving students' understanding and skills in prayer procedures. Therefore, this method can be used as a learning strategy that can be applied in Islamic religious education, especially in practical materials.